2000
DOI: 10.1002/chin.200027161
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: A New Route Toward 4‐Substituted Pyrazino[2,1‐b]quinazoline‐3,6‐dione Systems. Total Synthesis of Glyantrypine.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…6 Since Mantle's research group 7 isolated the glyantrypine-family alkaloids from the secondary metabolites of Aspergillus clavatus, it has been found that glyantrypine-family alkaloids had moderate cytotoxicity to leukemia cell line P388 8 and played an important role in the treatment of cardiovascular diseases, 9 influenza virus, 10 neuroprotection, 11 anticarcinoma, 12 and other aspects. The broad-spectrum biological activities and unique structural skeleton of these alkaloids have attracted the attention of synthetic chemists, and a series of synthetic methods of these alkaloids have been reported, which can be divided into two categories: the Eguchi aza Wittig synthetic method [13][14][15] and the Mazurkiewicz-Ganesan synthetic method. [16][17][18] In the Eguchi aza Wittig synthesis method, the pyrazine [2,1-b] quinazoline-3,-6-dione skeleton was synthesized by selective acylation of diketpiperazine with o-azido benzoyl chloride and cyclization.…”
Section: Introductionmentioning
confidence: 99%
“…6 Since Mantle's research group 7 isolated the glyantrypine-family alkaloids from the secondary metabolites of Aspergillus clavatus, it has been found that glyantrypine-family alkaloids had moderate cytotoxicity to leukemia cell line P388 8 and played an important role in the treatment of cardiovascular diseases, 9 influenza virus, 10 neuroprotection, 11 anticarcinoma, 12 and other aspects. The broad-spectrum biological activities and unique structural skeleton of these alkaloids have attracted the attention of synthetic chemists, and a series of synthetic methods of these alkaloids have been reported, which can be divided into two categories: the Eguchi aza Wittig synthetic method [13][14][15] and the Mazurkiewicz-Ganesan synthetic method. [16][17][18] In the Eguchi aza Wittig synthesis method, the pyrazine [2,1-b] quinazoline-3,-6-dione skeleton was synthesized by selective acylation of diketpiperazine with o-azido benzoyl chloride and cyclization.…”
Section: Introductionmentioning
confidence: 99%